Efficient Solar Tracking System for Optimum Power Output: A Review - Yousuf, Yawer; Kaur, Kiranpreet (Journal of Advanced Research in Alternative Energy, Environment and Ecology, 2020)
Power plants based on the solar concept are very important for areas facing electricity shortage. To address the electricity shortage it is very essential to deploy latest and emerging technologies like IoT to transfer the world into smart concepts like intelligent vehicles, power plants with smart machinery etc. The paper presents the review of smart and efficient solar tracking system with manual and automatic rotation of panels based on the intensity of lights. How to cite this article:  Yousuf Y, Kaur K. Efficient Solar Tracking System for Optimum Power Output: A Review. J Adv Res Alt Energ Env Eco 2020; 7(4): 21-25.